Peningkatan Hasil Belajar Membaca Peserta Didik Kelas 1 SDN 3 Gunungan Melalui Metode Make a match Tahun Pelajaran 2018/2019 - Kartinasih, Ari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to find out if the Make a match learning model can increase the motivation and the results of learning to read learners. To achieve that goal the study involves two cycles in stages of planning, execution, observation, and fermentation. Activity of action on each cycle is measured by observation and non testing. Based on actions made it may be concluded that the use of the Make a match model can increase the motivation and result of learning to read class 1 SDN 3 mountain learners year 2018/2019. This could be proved that the average on cytollus 54.33 increased on cycle 1 was 61.67, again on cycle ii average value to 81.5. The rating of systemic assessments on infrastructure at 20% increased by disiklus 1 to 46.67% and went from the second cycle to 80%.